ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN SUBSEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nada Arafah (2021)
This study aimed to determine the effect of the influence of the debt policy as measured by debt to equity, profitability as measured by return on assets and the size of the company measured by the logarithm natural of total assets to the value of the company as measured by price-book value on the company's property and real estate in Indonesia is listed on the Indonesia Stock Exchange in the 2015-2019 research year. The population in this study were all companies property and real estate listed on the Indonesia Stock Exchange, totaling 66 companies. The number of samples used in this study were 30 companies selected using purposive sampling method. The analysis technique used is Panel Data Regression Analysis with programs E-Views 10 and Microsoft Excel 2013. The results showed that debt policy had an effect on firm value, and profitability had no effect on firm value, while firm size had an effect on firm value.